2020
DOI: 10.1108/afr-04-2020-0054
|View full text |Cite
|
Sign up to set email alerts
|

Examining institutional credit access among agricultural households in Eastern India: trends, patterns and determinants

Abstract: PurposeThis paper is an attempt to understand the pattern of credit among agricultural households in Eastern India and to identify the correlates of their access to institutional credit for policy imperatives.Design/methodology/approachThe study uses unit-level data from the All-India Debt and Investment Survey of the 59th and 70th rounds of the National Sample Survey Office for the years 2002–2003 and 2012–2013. Cragg's double-hurdle model and the Heckman selection model are used to estimate the determinants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 33 publications
2
17
0
Order By: Relevance
“…In comparison to marginal land households, small and large land households are more likely to access credit from formal sources. Our results are consistent with the findings in the literature (Kumar, Singh, & Kumar, 2007; Kumar et al, 2015).…”
Section: Econometric Results and Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In comparison to marginal land households, small and large land households are more likely to access credit from formal sources. Our results are consistent with the findings in the literature (Kumar, Singh, & Kumar, 2007; Kumar et al, 2015).…”
Section: Econometric Results and Discussionsupporting
confidence: 94%
“…To overcome the agricultural distress, agricultural policies in India are made to ease the farmers’ access to credit across classes and regions. However, Kumar, Singh, and Sinha (2010) found that, in reality, a skewed distribution of formal credit across regions persists.…”
Section: Descriptive Results and Discussionmentioning
confidence: 99%
“…Although a multiagency, approach was envisaged to cater for the diverse credit needs of rural people. It has been suggested (Satyasai, 2008;Golait, 2007;Singh et al, 2009;Kumar et al, 2010;Sandhu Banks' lending practices et al, 2015;Bhattacharya, 2017;Khanal and Omobitan, 2020) that in reality, the rural clientele hardly benefited from multiple providers of finance as the system suffered from many infrastructural deficiencies. These structural and operational framework changes facilitated the process of institutionalisation and the regulation of the rural financial market in India to some extent.…”
Section: Banks' Lending Structurementioning
confidence: 99%
“…schemes in this regard that will enhance the productivity monetary status of the farmer's agricultural infrastructure warehousing facilities insurance against various extracts irrigation facilities and so on. Welfare of the farmers paved the way for the substantial growth of financial inclusion in the country [1][2]. Hope in the next decade if the government of India will focus on the growth of four key areas which will enhance income of the farmers and also reach the target then the overall welfare of productive sector becomes feasible [3].…”
Section: Page 233mentioning
confidence: 99%